KUALITAS MI BASAH DENGAN SUBSTITUSI JAGUNG - Irferamuna, Ade; Faridah, Anni; Kasmita, Kasmita (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2015)
Increased production of corn per year from 2011-2013. One way to optimize the useof corn can be done by substituting the flour in food processing. This study aimed to analyzethe quality of wet noodles with corn substitution as much as 0, 30, 40, and 50% that includesthe color, aroma, flavor, and texture. This type of research is pure experimentation (trueexperimentation) with a completely randomized design method of three repetitions. Resultsof hypothesis testing showed there are significant levels in each treatment. Quality producedgenerated in this study are quite yellow color, quite flavorful corn aroma, flavor was tastyenough and tasted enough maize, the texture is chewy and rather not easily broken. Based onhedonic test, panelists preferred the substitution of 30%. The best quality of wet noodles withcorn substitution is the noodle substitution of 30%.Keywords: corn, wet noodles, quality of wet noodle